Application of the Deductive Method in Nahwu Learning Based on the Book of Al-Muyassar Fi Ilmi `n-Nahwi by K.H Aceng Zakariya - Rifa'i, Ilyas; Ma'arif, Syamsul (UIN Sunan Gunung Djati Bandung, 2022)
This research departs from the background problem of nahwu learning, namely the difficulty of students in understanding nahwu learning based on the book of Al-Muyassar Fi Ilmi `n-Nahwi, besides learning Arabic at the Persis Ciganitri MA is using a branch system approach or Nadzariyatul Furu'.Therefore, researchers want to know how teachers prepare and manage nahwu learning, because in general Arabic learning at the Madrasah Aliyah level uses a unitary system approach or Nadzariyatul Wihdah.This study aims to determine how the objectives of learning nahwu based on the book of Al-Muyassar Fi Ilmi `n-Nahwithen aspects of planning, implementation, assessment techniques and supporting and inhibiting factors in nahwu learning.The research method used is a case study with descriptive qualitative methods. Data collection techniques in this study were observation, interviews and documentation.The results of this study explain that the purpose of learning nahwu at MA Persis Ciganitri based on the book of Al-Muyassar Fi Ilmi `n-Nahwiis to protect the mouth from pronunciation and writing errors, provide an understanding of the nahwu aspect and understand the position of the sentence, allowing students to be able to read and write. understand Arabic books or texts, especially in understanding the Qur'an and hadith.In the implementation of nahwu learning, the teacher uses the curriculum syllabus from the Central Leadership of the Islamic Union, and in the implementation of learning activities the teacher uses the deductive method, it's just that the teacher does not use a variety of learning media. Then the teacher uses nahwu learning assessment techniques such as: 1) observation, 2) tests, and 3) direct assessment. In addition, the teacher also conducts assessments: 1) weekly assessment, 2) Mid-semester Examination, and 3) Final Semester Examination 4) assessment of reading practice.Penelitian ini berangkat dari latar belakang masalah tentang pembelajaran nahwu, yaitu kesulitan siswa dalam memahami pembelajaran nahwu berbasis kitab Al-Muyassar Fi Ilmi `n-Nahwi, selain itu pembelajaran Bahasa Arab di MA Persis Ciganitri adalah menggunakan pendekatan sistem cabang atauNadzariyatul Furu’. Oleh karena itu, peneliti ingin mengetahui bagaimana cara guru mempersiapkan dan mengelola pembelajaran nahwu, karena pada umumnya pembelajaran bahasa Arab di tingkat Madrasah Aliyah menggunakan pendekatan sistem kesatuan atau Nadzariyatul Wihdah. Penelitian ini bertujuan untuk mengetahui begaimana tujuan pembelajaran nahwu berbasis kitab Al-Muyassar Fi Ilmi `n-Nahwikemudian aspek perencanaan, pelaksanaan, teknik penilaian dan faktor pendukung dan penghambat dalam pembelajaran nahwu. Adapun metode penelitian yang digunakan yaitu studi kasus dengan metode kualitatif deskriptif. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Hasil penelitian dalam penelitian ini menjelaskan bahwa tujuan pembelajaran nahwu di MA Persis Ciganitri berbasis kitab Al-Muyassar Fi Ilmi `n-Nahwiyaitu untuk menjaga lisan dari kesalahan pengucapan dan tulisan, memberikan pemahaman dari aspek nahwu dan memahami kedudukan kalimat, memungkinkan siswa untuk bisa membaca dan memahami kitab atau teks berbahasa arab terutama dalam memahami al-qur’an dan hadits. Dalam pelaksanaan pembelajaran nahwu, guru menggunakan silabus kurikulum dari Pimpinan Pusat Persatuan Islam, dan dalam pelaksanaan kegiatan pembelajaran guru menggunakan metode deduktif, hanya saja guru kurang menggunakan media pembelajaran yang beragam. Kemudianguru menggunakan teknik penilaian pembelajaran nahwu seperti: 1) observasi, 2) tes, dan 3) penilaian langsung. Selain itu guru juga melakukan penilaian: 1) penilaian mingguan, 2) Ujian Tengah Semester, dan 3) Ujian Akhir Semester 4) penilaian praktik membaca.